Merchandise Brand Image Analysis in Shaping Consumptive Lifestyle A Community of Fans - Dwinanda Pratya Annisa Murni; Rahma Wahdiniwaty (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this study is to determine whether the brand image of a product affects on the consumptive lifestyle of a fan community. This is because there is currently the most obvious example of a boy group from South Korea and their fans. Currently, the boy group is dominating the world-class music scene, so this causes fans to be crazy about them which ends up storming merchandise that can be sold out in seconds. The method used is a verification analysis with a survey using a questionnaire distributed online to fans of the boy group. The results of the study stated that from 200 respondents’ data collected, the brand image of the boy group’s products had an effect on the consumptive lifestyle of the fan community.